Pivmecillinam Treatment of Community-Acquired Uncomplicated Pyelonephritis Based on Sparse Data - Filip Jansaker; Frederik Boetius Hertz; Niels Frimodt-Moller; Jenny Dahl Knudsen (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2015)
Background: Pivmecillinam has good pharmacokinetic properties for treatment of infections in the urinary tract, and the mecillinam resistance rate in Enterobacteriaceae is very low. In a European guideline pivmecillinam is recommended as a first-line drug for treatment of lower urinary tract infections. In Danish and Norwegian guidelines pivmecillinam is also recommended for acute uncomplicated pyelonephritis, although with very sparse documentation of effect. Objectives: We intended to investigate the therapeutic outcome of pivmecillinam treatment of uncomplicated pyelonephritis caused by Enterobacteriaceae treated by general practitioners (GP's) in primary care. Material and methods: We included patients clinically diagnosed with pyelonephritis at the GP, urine samples positive for Enterobacteriaceae and empirical treatment with pivmecillinam. We intended to include patients prospectively, but due to slow inclusion we also included patients retrospectively. The prospectively included patients were asked to fill out a questionnaire and submit control urine samples. The retrospectively included patients were followed by available urine samples and the text on the requisition only. The patients were followed by their urine samples for three months. Results: We identified 22 patients (i.e. six patients prospectively and found another 16 patients retrospectively). Bacterial and clinical cure rate was 77% (95%c.i.: 60-95%), respectively. In seven (32%) of the patients, we observed a recurrent or new infection within three months. Conclusion: There is indication for safe oral treatment with pivmecillinam in uncomplicated pyelonephritis caused by a mecillinam susceptible E. coli. More studies and especially prospective and randomized clinical studies are needed before pivmecillinam can be recommended as first line option for treatment of pyelonephritis.